A highly selective colorimetric and long‐wavelength fluorescent probe for the detection of Hg2+. (8th July 2018) - Xu, Jing; Wang, Zuokai; Liu, Caiyun; Xu, Zhenghe; Wang, Ning; Cong, Xin; Zhu, Baocun
Abstract: Currently, the fluorescent probe is an important method for detecting heavy metal ions, especially mercury ion (Hg 2+ ), which is harmful to the health of humans and the environment due to its toxicity and extensive use. In this paper, we designed and synthesized a colorimetric and long‐wavelength fluorescent probe Hg‐P with high sensitivity and excellent selectivity, which could detect Hg 2+ by the changes of visual color, fluorescence and absorption spectroscopy. With the addition of Hg 2+ to probe Hg‐P solution, its color changed from yellow to pink, and showed a 171 nm red‐shifted absorption spectrum. Probe Hg‐P was used in real water and soil solution samples to detect Hg 2+, and the result is satisfactory. Therefore, this new probe shows great value and application in detecting Hg 2+ in the environment.